BIKE WORKING ON WATE - Prof S.B.Deshmukh,; Santosh Rajendra Gaikwad,; Yashraj Chandrakant Baviskar,; Vaibhav Babasaheb Dhanwate,; Yagnik Vinay Patel, (International Journal of Innovations in Engineering Research and Technology, 2021)
H2O otherwise known as hydroxy or Browns Gas is the gas produced from splitting water into hydrogen and oxygen from electrolysis and allowing the gas to stay in a premixed state for use on-demand without the need for storage. In 1918 Charles Frazer, a North American inventor, patented the first water electrolysis machine act as a hydrogen booster for internal combustion engines. Yull Brown, a Bulgarian born Australian inventor patented and attempted to popularize Browns Gas as a cutting gas and fuel additive during the 1970’s and 80’s. During the 2000’s there was a huge influx in Browns Gas devices coming to the mark, with many sensational claims of bringing dramatic reductions in fuel consumption and exhaust emissions in internal combustion engines.